Effect of ANA and BAP on ginger (Zingiber officinale Roscoe) sprouting in solid and liquid medium (Revista Brasileira de Plantas Medicinais, 2000)
This work evaluated the in vitro growth and development of ginger explants submitted to different levels of NAA (0 - 0.25 - 0.5 - 0.75 - 1.0 mg/L) or BAP (0 - 0.5 -1.0- 1.5 - 2.0 mg/L) in solid and liquid medium, followed by the growth in the best combination of these growth regulators (0 and 0.5 mg/L NAA plus 0 and 1.0 mg/L BAP). NAA increased the shoots length in both solid and liquid medium. Maximum effect of NAA on the number and length of roots was achieved at concentration of 0.5 mg/L. BAP effected significantly the number of shoots in both media, with maximum response at 1.0 mg/L. In liquid medium the absence of BAP induced higher number of shoots and the length of shoots was affected by NAA and BAP, with best effects at 1.0 mg/L BAP, 0.5 mg/L and control. Root number and length were enhanced in liquid medium regardless the growth regulator treatment.